Biomechanics of biomaterials used in soft tissue regenerative medicine - A. F. C. Vieira (2009)
Biodegradable polymers have been used in implantable medical devices, such as suture fibers, fixation screws and soft tissue engineering devices. Apart from biological compatibility, these devices shall also be functional compatible and perform adequate mechanical temporary support during the healing process. In regenerative medicine, the scaffold that will provide this temporary support should simultaneously enhance cellular adhesion, proliferation and remodeling of new tissue. In soft tissue applications, biodegradable polymers are the materials of election. These materials undergo through a process of degradation, mainly controlled by hydrolysis, leading to a reduction of molecular weight, followed by reduction of strength and finally a reduction of mass until it is totally absorbed and assimilated by the host. Fatigue/creep damage also contribute to the progressive decrease of mechanical properties. Meanwhile, cells cultured over the scaffold will produce the new tissue that will gradually replace the material biomechanical functions.